INVESTIGATION OF THE OPTIMIZATION PROCESS OF LASER SURFACE MARKING ON POLYAMIDE SAMPLES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Give Thermoplastic laser marking technology is becoming increasingly popular in the electronics industry. Using marking codes requires more information to store, which requires the marking to be of good contrast and durability over time. The main goal of the research was to achieve high-quality marking on polyamide surfaces. A nanosecond fiber laser was used to laser mark polyamide samples. An experimental marking matrix of 8 columns and 6 rows was developed, respectively varying the marking step, scanning speed, marking repeats. The dimensions of the marked squares are 10×10 mm. Surface changes and marking quality were examined using a laser scanning microscope. Markings with good contrast were found, as well as marking modes with partial and full melting modes. Roughness and contrast were measured for the optimal marking modes. Graphical dependences are constructed for the effect of roughness and contrast on propagation speed and distance in laser marking. For the study, the average laser power was fixed. During the experiment, it was found that laser marking on polyamide can lead to different shades of gray and yellow, and the surface after laser treatment has become rougher.